NOTE ON THE GEOLOGY OF THE PROTEROZOIC RAYNER COMPLEX AT MT. VECHERNYAYA NEAR MOLODEZHNAYA STATION, ENDERBY LAND - マキモト, ヒロシ; アサミ, マサオ /; MAKIMOTO, Hiroshi; ASAMI, Masao; GREW, Edward S. (National Institute of Polar Research, 1989)
P(論文) Geological reconnaissance of the Proterozoic Rayner Complex was carried out at Mt. Vechernyaya in western Enderby Land during the 29th Japanese Antarctic Research Expedition (JARE-29,1987-1988) from February 14th to 17th, 1988. Mt. Vechernyaya (272m above sea level), situated on the coast of Alasheyev Bight, is about 10km east of Molodezhnaya Station.The basement around Mt. Vechernyaya consists mainly of granulite-facies, locally migmatitic, well-layered gneisses and charnockitic gneiss. The well-layered gneisses include garnet-biotite gneiss, clinopyroxene gneiss, hornblende gneiss and quartzo-feldspathic gneiss. Gneissosity trends E-W to ESE-WNW, and dips steeply to the north. Lineations, due to the preferred orientation of the mafic minerals, dip 5 to 20°east. Typical mineral assemblages of the garnet-biotite gneiss are Bi-Gt, Bi-Gt-Sil, Bi-Gt-Sil-Crd and Bi-Gt-Opx-Mt. The above cordierite-bearing assemblage is the third report from the Molodezhnaya area. Six well-layered gneisses were sampled for geochronological studies. The charnockitic gneiss, which is exposed in an elongate body, has mineral lineations but no marked compositional layering. Its intrusive relation with the well-layered gneisses suggests an igneous origin. This rock consists mainly of quartz, K-feldspar and plagioclase with minor orthopyroxene, clinopyroxene, hornblende and biotite.Granite and pegmatite dikes, a few centimeters to 1m thick, intrude the metamorphic rocks and charnockitic gneiss throughout the area. departmental bulletin paper